Migration and foreign aid: Drivers, desires and development - Ida Marie Savio Vammen; Lars Engberg-Pedersen; Hans Lucht (Danish Institute for International Studies (DIIS), 2021)
In the debate in Europe, conflict, lack of development, population growth, and climate change are often described as the 'root causes' of African migration. However, recent research-based literature on the links between migration and development stands in stark contrast to such simplified assumptions. This working paper explores the relationship between migration, development, and foreign aid. It builds on insights from both quantitative and qualitative studies focusing on Africa - especially West Africa - and is divided into three parts. It first examines the factors that underpin human mobility, then looks at contemporary African migration trajectories, and finally discusses how migration relates to foreign aid. The working paper argues that foreign aid initiatives often focus on externally defined root causes of migration and rarely attempt to understand locally determined drivers of migration. To better grasp how development policies and migration intersect, more in-depth research is needed.
Keywords: 330; Migration and development; Development policy; Inequality and poverty; Danish and European foreign policies